Intravitreal connective tissue growth factor neutralizing antibody or bevacizumab alone or in combination for prevention of proliferative vitreoretinopathy in an experimental model. (July 2021) - Daftarian, Narsis; Baigy, Omolbanin; Suri, Fatemeh; Kanavi, Mozhgan Rezaei; Balagholi, Sahar; Afsar Aski, Sasha; Moghaddasi, Afrooz; Nourinia, Ramin; Abtahi, Seyed-Hossein; Ahmadieh, Hamid
Abstract: Connective tissue growth factor (CTGF) is released by retinal pigment epithelial (RPE) cells and detectable in proliferative membranes (PrMs). This experimental study was performed to investigate the mRNA and protein levels of both CTGF and vascular endothelial growth factor A (VEGF-A) in a rabbit model of proliferative vitreoretinopathy (PVR). In addition, the effects of a single intravitreal injection of the safe dose of anti-CTGF or bevacizumab as monotherapy and in combination were evaluated. PVR was induced in the right eye of albino rabbits by intravitreal injection of cultured adult human RPE cells. Quantitative real-time reverse transcription PCR (qRT-PCR) and Western blot analysis of CTGF and VEGF-A were performed on whole eye tissue in the PVR model versus controls at different time points. In the next step, the PVR models were assigned to five groups. The monotherapy groups received a single intravitreal injection of 0.1 ml of anti-CTGF 100 μg/ml (final concentration of 6.6 μg/ml in the vitreous) or 0.03 ml of 25 mg/ml bevacizumab. In the combined group, the abovementioned amounts of anti-CTGF and bevacizumab were injected intravitreally from separate sites in one session. No antibody injection was performed in the control group. Intravitreal injection of 0.1 ml of control IgG (1 mg/ml of isotype matched) antibody was performed in the placebo group. After 2 weeks, histologic evaluation including, trichrome staining for collagen, immunostaining by anti-alpha-smooth muscle actin for myofibroblasts, and anti-collagen type-1 antibody on paraffin embedded anterior-posterior sections was done. In addition, fundus photography was performed for clinically equivalent PVR staging. Twenty-four hours following PVR induction, CTGF mRNA and protein levels increased five- and- three-fold compared to controls, respectively (P < 0.001). VEGF-A mRNA and protein levels decreased significantly after 72 h of PVR induction compared to controls (P < 0.05). Means of PrM thickness and myofibroblast cell counts significantly decreased in the anti-CTGF group (P < 0.001 and P < 0.05, respectively). The mean area of collagen type-1 fibers of PrM in the mono- and combination therapy groups that received intravitreal anti-CTGF was significantly reduced (P < 0.001); in addition, mild PVR (stage-1 and 2) formation occurred in comparison with moderate to severe PVR (stage-4 and higher) in other groups. In conclusion, we found that intravitreal injection of CTGF neutralizing antibody resulted in a reduction in PrM thickness, collagen fibers and myofibroblast density in the PVR model. CTGF inhibition may represent a potential therapeutic target for PVR. Highlights: There was a significant increase in CTGF mRNA and protein levels following induction of PVR in our rabbit model. Mean thickness of proliferative membranes (PrMs) was lower in anti-CTGF treated eyes as compared to control eyes. Myofibroblast cells were decreased significantly in anti-CTGF treated eyes as compared to control eyes. Intravitreal anti-CTGF more effectively decreased the mean area of collagen type-1 fibers inside PrMs compared to anti-VEGF.